Beneficial Effects of Rhizobacterial Inoculation on Nutrient Uptake, Growth and Yield of Banana (Musa Spp. Cv. 'Berangan') - Mia, Md. Abdul Baset (2002)
Banana, an important fruit crop, requires high amounts of N-fertilizers for commercial cultivation, which is costly and can be hazardous to the environment when used excessively. Biofertilizer is globally accepted as an alternative source of nitrogen fertilizer and can substantially supplement the N requirement while enhancing the uptake of water and mineral nutrients of crop plants. A series of research study involving six experiments were conducted to observe the effects of PGPR inoculation on root stimulation and colonization, nutrient absorPtion, growth, yield and fruit quality of bananas (Musa spp cv 'Berangan', AA type) under hydroponics condition. In the preliminary study, the effects of inoculation with two PGPR strains, Sp7 (Azospirillum brasilense) and UPMB10 (Bacillus sphaericus UPMB10), on plant growth and N accumulation of banana plantlets were observed under N-free hydroponics condition for 45 days. A marked increase in root growth namely length (33-44%), volume (76-168%) and mass (137-141%) were recorded due to the PGPR inoculation besides a higher shoot growth (123-202%) and N yield (94-144%). An in vitro electron microscopy study was conducted to observe the pattern of colonization ofPGPR strains Sp7 and UPMBI0 on roots of banana plantlets. This study demonstrated that both strains could effectively colonize the banana roots and more bacterial cells were present in the root hair proliferation zone. In the growth study with banana plantlets under hydroponics condition using 4.0 L plastic pots,] 50 ppm fertilizer-N was found to be optimum for the 45 days period. Another study with similar conditions was undertaken to observe the synergistic effect of minimal fertilizer-N supply (33% of the total N requirement) and PGPR inoculation on root growth and nutrient uptake of banana plantlets. The results showed that inoculation by UPMB10 with minimal fertilizer-N supply increased the primary root elongation and secondary root initiation and subsequently increased the root mass. The same treatment also increased N concentration in pseudostem and leaves and Ca concentration in roots. The total accumulation of N, P, K, Ca and Mg was increased due to inoculation; a consequence of increased plant growth. Plants with this treatment produced an equivalent total dry matter as those supplied with 100% N.